Deep Vein Thrombosis : An Unusual Presentation in COVID- 19 Patients-Our Experience and Comparison with Non COVID-19 Deep Vein Thrombosis Cases - Vaidya, Satish; Karmacharya, Robin Man; Bhandari, Neetu; Hada, Gonish; Sah, Shushil; Bade, Sahil; Sedhai, Swastika (Annapurna Journal of Health Sciences, 2023)
Introduction: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) was found in Wuhan China which caused the acute respiratory illness and became the pandemic as declared by World Health Organization on March 11, 2020. Viral inclusion bodies have been identified in endothelial cells in a variety of organs. Deep Vein Thrombosis(DVT) is one atypical presentation which is thought to be triggered by endothelial dysfunction and exacerbated by hypoxia in patients with COVID-19. Methods: It was a single center retrospective study in Kathmandu University Dhulikhel Hospital. All the data were taken between January, 2020 till May, 2021 who were presented in OPD or inpatient department with symptoms of DVT and required admission. Presence or absence or concomitant COVID-19 was tested by RT-PCR test. Result: There were a total of 52 patients admitted as DVT, among which 26(50%) were male and 26(50%) were female. Twenty patients (38.5%) were COVID-19 positive and 32 (61.5%) were COVID-19 negative. Mean age for among those patients was 50.50±4.8 years, average hospital stay was 6.4±0.6 days, after anticoagulation therapy target INR was reached in 3.8±0.17 days and CVI was present in 14(70%) for COVID positive with DVT. Similarly, mean age was 46.80±3.3 years, average hospital stay was 4.6±0.3 days, after anticoagulation therapy target INR was reached in 3.3±0.21 days and CVI was present in 18(56.65%) with COVID negative with DVT. Conclusion: COVID-19 is still the mysterious virus and exact mechanism of this disease is still a debate which may need many years to solve. Sometimes DVT can be the only presentation of this disease.